Reconciliation of Orebody Model Predictions – System and People - T Burns; P Savory (The Australasian Institute of Mining and Metallurgy, 2014)
In 2013, Rio Tinto Iron Ore (RTIO) produced 251 Mt from 15 mines in Western Australia. Throughout the mines, Ore Reserve models are used for long-term and medium-term mine planning. Grade control data aids the accuracy of short-term planning. Reconciliation of models with grade control data is important for maintaining confidence in predictions from the models, understanding the limitations of the models, and identifying issues that may require further work.There are a large number of sites and models, with more than 200 professionals involved in different parts of the reconciliation process. Regular meetings of all involved and enabling effective communication are important in the reconciliation process.Reconciliation data is gathered and processed through a web-based system; Grade Block Reconciliation System. This system cuts each grade block against the required model, stores the results, and allows users to view and analyse the data. Development of this system has occurred over a number of years and all Rio Tinto Iron Ore mine geologists and resource geologists now use it as standard to report reconciliation results. The results can be viewed in many ways including by different time periods or benches. Graphing the results assists identification of trends. Centralising and standardising reconciliation has allowed easier comparison between sites. Flexibility in the system allows users to customise reports to manage issues unique to their particular site.In parallel with system development, substantial effort has been put into ensuring mining professionals get together to discuss and understand reconciliation issues. To facilitate this there are now regular sessions, including site visits. Issues are assessed on a case-by-case basis and decisions on how best to address the issues are made by the relevant stakeholders. Reconciliation reports and action plans are revised each quarter.CITATION:Burns, T and Savory, P, 2014. Reconciliation of orebody model predictions – system and people, in Proceedings Ninth International Mining Geology Conference 2014 , pp 367–376 (The Australasian Institute of Mining and Metallurgy: Melbourne).